PENGGUNAAN PASIR DAN KERIKIL SILIKA DARI SISA PENAMBANGAN BATU KAPUR SEBAGAI SUBSTITUSI AGREGAT UNTUK PERKERASAN JALAN KAKU - Suhelmidawati, Etri; Yaldi, Gusri; Mirani, Zulfira; Yufajri, Fahmiza; Ikhsan, Muhammad (Jurnal Jalan Jembatan, 2023)
The purpose of this study is to determine the effects of using silica sand and gravel in concrete as a substitution of coarse aggregates and fine aggregates and to increase the value of compressive strength and flexural strength in concrete for road pavement. This study applied the experimental methods, including material testing, compressive strength and concrete flexural strength testing, referring to the American Standard Testing and Materials (ASTM). From the test results, the highest compressive strength value of concrete was obtained from the 3rd concrete variation with a concrete mixture of 100% silica sand + natural gravel + sikament NN with a compressive strength value of 41.14 MPa. The optimum flexural strength value is obtained from the concrete mix in the 4th variation, namely 100% natural sand + silica gravel + sikament NN with a flexural strength value of 1.6 MPa. Based on these results, the 4th concrete variation was chosen to be applied on the basis of its optimum flexural strength value and compressive strength value that exceeds the design compressive strength, namely 32.36 MPa (fc' design 30 MPa). Manual Desain Perkerasan (MDP) 2017 is used to design rigid pavement on Aia Anak Simpang Road – Minangkabau International Airport Fly Over STA 22+800 to STA 22+800. The pavement thickness obtained is 27.5 cm. Therefore, silica sand and gravel can increase the compressive strength of normal concrete after the addition of silica material, play a role in resisting cracks in cylindrical specimens.